Radicalism Interpretation of Verses of Blasphemy: Review of The Khawārij Sect’s Interpretation - Heriyanto (JURNAL PENELITIAN, 2018)
This study questions the response of the Khawārij sect in interpreting the verses that speak of blasphemy. The study will focused on exploring the results of the Khawārij interpretation of the blasphemy verses in the Tafsīr Haimayan al-Zād Ilā Dār al-Ma’ād by Yusuf Wahbi, this book was chosen because it became a reference often used by the Khawārij sect to this contemporary period. For this reason, the author tries to use the Gadamer-style hermeneuticsubjectivist approach so that the ideological dimension in the interpretation can be properly embodied. The results of the study indicate that Khawārij tends to be textual and put forward their ideology in interpreting the verses of blasphemy. This is evidenced by the existence of a bid'ah instrument which is used as a benchmark to set a ban on sitting with the perpetrators such as the prohibition of sitting with people who deny and insult the Qur'an as in QS. Al-Nisa ': 140. In addition, the results of the interpretation of Khawārij have reduced the preventive principle contained in QS. Al-An'am 108 and their interpretation of QS. Al-Taubah: 12 has indirectly opened the opportunity for the creation of excessive arrogance against religious offenders.